2002
DOI: 10.1093/oxfordjournals.jbchem.a003246
|View full text |Cite
|
Sign up to set email alerts
|

KIF1B 2, Capable of Interacting with CHP, Is Localized to Synaptic Vesicles

Abstract: Kinesin family proteins are microtubule-dependent molecular motors involved in the intracellular motile process. Using a Ca2+ -binding protein, CHP (calcineurin B homologous protein), as a bait for yeast two hybrid screening, we identified a novel kinesin-related protein, KIF1Bbeta2. KIF1Bbeta2 is a member of the KIF1 subfamily of kinesin-related proteins, and consists of an amino terminal KIF1B-type motor domain followed by a tail region highly similar to that of KIF1A. CHP binds to regions adjacent to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…50 Interestingly, Szolnoki et al, 51 showed that cognitive deficit in hypertensive smokers is related to the presence of polymorphisms in the kinesin gene, which may be related to the findings of this study in which the expression of kinesin 1Bbeta is 70% lower in SHR cells as compared with WKY and nicotine increased it in SHR and decreased it in WKY cells.…”
Section: Nicotine Regulates Gene Expression Of Brainstem Cells Discussupporting
confidence: 62%
“…50 Interestingly, Szolnoki et al, 51 showed that cognitive deficit in hypertensive smokers is related to the presence of polymorphisms in the kinesin gene, which may be related to the findings of this study in which the expression of kinesin 1Bbeta is 70% lower in SHR cells as compared with WKY and nicotine increased it in SHR and decreased it in WKY cells.…”
Section: Nicotine Regulates Gene Expression Of Brainstem Cells Discussupporting
confidence: 62%
“…It was initially identified as a protein (p22) involved in vesicular transport (15) and the inhibition of calcineurin phosphatase activity (16). It was also found to interact with microtubules (17), DRAK2 (death-associated protein kinaserelated apoptosis-inducing protein kinase 2) (18) and KIF1B␤2 (kinesin family 1B␤2) (19).…”
Section: /Hmentioning
confidence: 99%
“…3B). The secondary structure consists of ␣A (residues [11][12][13][14][15][16][17][18][19][20][21][22], ␣B (residues 26 -37), ␣C (residues 48 -51), ␣D (residues 64 -70), ␣E (residues 80 -88), ␣F (residues 111-122), ␣G (residues 132-143), ␣H (residues 149 -162), ␣I (residues 174 -180), and ␣J (residues 185-188) (Figs. 1B and 3B).…”
Section: Journal Of Biological Chemistry 2743mentioning
confidence: 99%
“…Both rCHPs were found in the cytoplasm and also accumulated predominantly in a juxtanuclear region in which the Golgi and microtubule-organizing center are present. Since CHP1 has been shown to associate with microtubules and KIF1Bb2, one of kinesin moter proteins, 39,40) the accumulation of rCHPs in the juxtanuclear region may result from the microtubule-association. Although the localization of the two rCHPs was similar in the cytoplasm and juxtanuclear region, the fluorescence intensities of the two rCHPs were different in the region stained with Hoechst33342, a nuclear-staining dye (Fig.…”
Section: Intracellular Distribution Of Rchp2mentioning
confidence: 99%